PENGARUH MODAL PSIKOLOGIS, PO-FIT DAN EMPLOYEE ENGAGEMENT TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA AKPOL SEMARANG - Souisa, Johanis; Rizkiana, Citra; Yani, Tri Endang (Fakultas Ekonomi, Universitas Semarang, 2021)
The purpose of this study was to examine and describe the effect of Psychological Capital, Person Organizational Fit (PO-Fit) and Employee Engagement on Organizational Citizenship Behavior (OCB) in the MANAGE section of the Semarang Police Academy Police. Samples were taken as many as 100 employees, while the sampling technique used was the Saturated Sample method. The data analysis technique was carried out using Multiple Linear Regression. With descriptive analysis method, the data analysis technique in this study used the SPSS 21.00 program. Hypothesis testing shows that there is a significant effect of Psychological Capital, Person Organizational Fit (PO-Fit) and Employee Engagement on Organizational Citizenship Behavior (OCB). Keywords: Psychological Capital, Person Organizational Fit (PO-Fit), Employee Engagement, Organizational Citizenship Behavior (OCB),